Event-Driven Immunoprofiling Predicts Return of Disease Activity in Alemtuzumab-Treated Multiple Sclerosis - Akgün, Katja; Blankenburg, Judith; Marggraf, Michaela; Haase, Rocco; Ziemssen, Tjalf (Frontiers in Immunology, 2020)
Background: Alemtuzumab is a highly effective drug for the treatment of multiple sclerosis (MS), characterised by specific patterns of depletion and repopulation. As an induction-like treatment concept, two mandatory infusion courses can inhibit long-term disease activity in the majority of patients, and additional courses can successfully manage subsequent re-emergence of disease activity. Currently, there are no biomarkers to identify patients with re-emergent disease activity requiring retreatment. Methods: In this study, we systematically characterized 16 MS patients commencing alemtuzumab. Clinical parameters, MRI and detailed immunoprofiling were conducted every three months for up to 84 months. Results: Alemtuzumab led to significant decrease in clinical disease activity in all evaluated patients. 9 out of 16 patients presented with no evidence of disease activity (NEDA)-3 up to 84 months (‘super-responder’), while 7 patients demonstrated clinical or/and subclinical MRI disease activity and received alemutzumab retreatment (‘partial-responder’). In both response categories, all T- and B-cell subsets were markedly depleted after alemtuzumab therapy. In particular, absolute numbers of Th1 and Th17 cells were markedly decreased and remained stable below baseline levels – this effect was particularly pronounced in super-responders. While mean cell numbers did not differ significantly between groups, analysis of event-driven immunoprofiling demonstrated that absolute numbers of Th1 and Th17 cells showed a reproducible increase starting 6 months before relapse activity. This change appears to predict emergent disease activity compared when compared with stable disease. Conclusion: Studies with larger patient populations are needed to confirm that frequent immunoprofiling may assist in evaluating clinical decision-making of alemtuzumab retreatment.